Effect Of Nd:YAG Laser On Ants (Camponotus consobrinus) - Mahdi, Estabraq Mahmood; Rashid, Sahar Naji; Jasim, Awatif Sabir (Iraqi Journal of Science, 2021)
The subject of biophysics is interdisciplinary and covers various fields of biology and physics. In this research the effect of some parameters of Nd:YAG laser on ants (Camponotus consobrinus) has been studied . This includes the effect on its external shape, as well as the percentage of the killing rate obtained. A laser radiation of a wavelength (1.064 µm) with different energies: (300, 320, 340, 360, 380 and 480 mJ) was used to irradiate ants placed at a distance of (10 cm) distance from the laser source . The irradiation times were (15 and 20 sec) for each energy. The obtained results showed an increase in the rate of ant mortality, as well as an increase in deformations, as the laser energy and the irradiation time increased. These results were recorded after different time periods (12, 24, 48 and 72 hours) after laser treatment.. The thermal diffusion within the tissues resulting from laser radiation causes increased death rates due to damage of internal structures.